Geometry and discrete mathematics a selection of highlights - Fine, Benjamin 1948-; Moldenhauer, Anja; Rosenberger, Gerhard 1944-; Schürenberg, Annika; Wienke, Leonard (De Gruyter, 2022)
In the two-volume set 'A Selection of Highlights' we present basics of mathematics in an exciting and pedagogically sound way. This volume examines many fundamental results in Geometry and Discrete Mathematics along with their proofs and their history. In the second edition we include a new chapter on Topological Data Analysis and enhanced the chapter on Graph Theory for solving further classical problems such as the Traveling Salesman Problem
Keywords: Elementare Zahlentheorie; Galois-Theorie; Polynom; Primzahl; Zahlensystem; MATHEMATICS / Geometry / General